Diagnostic use of autoantibodies in myasthenia gravis. - Leite, M; Waters, P; Vincent, A (2010)
The diagnostic use of antibodies is dependent on sensitivity and specificity of the methods of antibody detection, which have been developed and improved over the years. Here, we review the different methods for the detection of acetylcholine receptor and muscle-specific kinase antibodies, which are, so far, the only antibodies recognised as pathogenic in myasthenia gravis (MG). Seronegative MG patients will benefit from more sensitive methods of antibody detection. The most recent developments in antibody detection assays, particularly those based on cells expressing target antigens, allow rapid and reliable identification of autoantibodies, improving the diagnosis and treatment of MG patients. The same approaches to antibody detection are now being applied to a wide range of other autoantigens and other autoimmune diseases.